2015
DOI: 10.4161/21645515.2014.990859
|View full text |Cite
|
Sign up to set email alerts
|

ISCOMATRIX™ adjuvant reduces mucosal tolerance for effective pulmonary vaccination against influenza

Abstract: While most pathogens infect via mucosal surfaces, most current vaccines are delivered by injection. This situation remains despite awareness of the potential benefits of mucosal delivery for inducing protection against mucosa-infecting pathogens. A major obstacle to the development of such vaccines is the paucity of safe and effective adjuvants that induce mucosal responses in non-rodents. Previously we demonstrated in sheep the potency of pulmonary-delivered influenza ISCOMATRIX™ vaccine, which induces both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…In addition, the CpG adjuvant prevented the increase in the ratio of antigen-specific Treg cells upon secondary immunization in mice primed by peptide alone, but did not suppress antigen-specific Treg cells to a level as low as that induced by CpG priming. Consistent with our observation, Timothy et al 32 also found that prior vaccination in lung mucosa with unadjuvanted influenza antigen alone induces Treg cells that significantly reduce the immune response to subsequent pulmonary-delivered influenza ISCOMATRIX TM -adjuvanted vaccine. Taken together, our data suggest that antigen-specific Tregs induced by an initial suboptimal vaccination strategy have detrimental effect on the immune response induced by effective adjuvanted vaccines.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the CpG adjuvant prevented the increase in the ratio of antigen-specific Treg cells upon secondary immunization in mice primed by peptide alone, but did not suppress antigen-specific Treg cells to a level as low as that induced by CpG priming. Consistent with our observation, Timothy et al 32 also found that prior vaccination in lung mucosa with unadjuvanted influenza antigen alone induces Treg cells that significantly reduce the immune response to subsequent pulmonary-delivered influenza ISCOMATRIX TM -adjuvanted vaccine. Taken together, our data suggest that antigen-specific Tregs induced by an initial suboptimal vaccination strategy have detrimental effect on the immune response induced by effective adjuvanted vaccines.…”
Section: Discussionsupporting
confidence: 92%
“…time, such administration can induce both long-lasting systemic and mucosal immune responses against respiratory pathogens (Timothy et al, 2015;Perdomo et al, 2016;Wu et al, 2017;Florido et al, 2018). Therefore, pulmonary vaccine delivery has received a lot of attention in recent studies (Guillon et al, 2012;Lee et al, 2012).…”
Section: Primer or Primer Pairmentioning
confidence: 99%
“…The lungs have a large surface area, abundant blood flow, and highly permeable epithelium, so vaccines administered via the lung show better bioavailability and more rapid onset time than other alternative routes (Patton et al, 2004 ; Patton and Byron, 2007 ; Lee et al, 2012 ; Kunda et al, 2013 ). At the same time, such administration can induce both long-lasting systemic and mucosal immune responses against respiratory pathogens (Timothy et al, 2015 ; Perdomo et al, 2016 ; Wu et al, 2017 ; Florido et al, 2018 ). Therefore, pulmonary vaccine delivery has received a lot of attention in recent studies (Guillon et al, 2012 ; Lee et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvants play pivotal roles in cell signaling, stimulating the innate immunity in the preamble to a robust antigen-specific adaptive immunity. Without the presence of an adjuvant, an antigen may induce immune tolerance rather than activating the immune system ( 3 5 ). Therefore, it is essential to co-deliver an adjuvant with an antigen to induce a desired immune response.…”
Section: Introductionmentioning
confidence: 99%